EVALUATION OF SOME IMMUNE PARAMETERS FOR PREGNANT WOMEN IN THE FIRST THREE MONTHS WHO ARE INFECTED WITH TOXOPLASMOSIS - Saja Younis Dals; Marwa Jassim Muhammad (European Science Publishing, 2024)
The aims of this study is to determine the prevalence of toxoplasmosis infection in pregnant women during the first three months of pregnancy in Salah Al-Din, Iraq, from August 1, 2023, until February 1 2024. The sample examined by studying 203 sample, 123 samples (60.59%) were positive, and 80 (39.04%) samples were negative for antibodies. The current study examined 90 optical ELISA techniques, The highest percentage of IgM infection was recorded when there were no cats (43.75%), while the lowest percentage of infection was recorded (56.25%). As for the IgG, the highest percentage reached when cats were present (74.66%), and the lowest percentage reached when cats were not present (25.33%). the epidemic it was recorded from the current study that the highest percentage of IgM (81.25%) for infection with Toxoplasma gondii was in women who had miscarried, while the percentage decreased to (18.75%) in non-aborted women. As for IgG, the percentage also increased in women who had miscarried (72%). IFN-γ Its concentration increased (20.6±85.9 pg/ml) in infected women while its decreased (22.0±63.8pg/ml) In uninfected women. CCR5 Its concentration decreased (185.4±19.5 pg/ml) in infected women, while its concentration increased (185.4±19.5pg/ml). (284.0±28.1 pg/ml)in uninfected women
Keywords: Gondii, Toxoplasma gondii, Interferon gamma, chemokine receptor typr5 ,ELISA IgG ,IgM.